State of the art in coronary revascularization: Everolimus eluting stents versus multiple arterial grafting. (15th September 2016) - Benedetto, Umberto; Caputo, Massimo; Vohra, Hunaid; Bryan, Alan; Angelini, Gianni D.
Abstract: Background: Contemporary comparisons on coronary revascularization should take into account the state of the art percutaneous coronary intervention (PCI) with new generation everolimus-eluting stents (EESs) and coronary artery bypass grafting (CABG) with multiple arterial grafts (MAGs). We aimed to compare early outcomes and late survival after EES versus MAG in patients with multivessel coronary artery disease using a single centre institutional database. Methods: In an observational registry study, we identified 3787 patients with multivessel coronary disease. Of these 696 (18.3%) underwent PCI with EES and 3091 (81.7%) CABG with MAG. With the use of propensity-score matching, we identified 483 pairs for final comparison (C-statistic: 0.91). Results: The two groups were comparable for 30-day mortality (1.6% versus 0.8% in the EES and MAG group respectively, P = 0.38). Stroke was not observed in the EES group and it was 0.8% in the MAG group (P = 0.13). After a mean follow-up of 3.1 years, PCI with EES was associated with a higher risk of late death (HR 2.2; 95% CI 1.18–4.16; P = 0.01). Conclusions: In patients with multivessel coronary disease, CABG with multiple arterial grafts when compared with PCI with new generation drug eluting stent, was associated with significantly improved long-term survival. Further randomized studies are warranted to identify the best revascularization strategies in the current era.